EGFR Amplification and IDH Mutations in Glioblastoma Patients of the Northeast of Morocco. (13th July 2017) - Senhaji, Nadia; Louati, Sara; Chbani, Laila; El Fatemi, Hind; Hammas, Nawal; Mikou, Karima; Maaroufi, Mustapha; Benzagmout, Mohammed; Boujraf, Said; El Bardai, Sanae; Giry, Marine; Marie, Yannick; et al.
Abstract : Glioblastomas are the most frequent and aggressive primary brain tumors which are expressing various evolutions, aggressiveness, and prognosis. Thus, the 2007 World Health Organization classification based solely on the histological criteria is no longer sufficient. It should be complemented by molecular analysis for a true histomolecular classification. The new 2016 WHO classification of tumors of the central nervous system uses molecular parameters in addition to histology to reclassify these tumors and reduce the interobserver variability. The aim of this study is to determine the prevalence of IDH mutations and EGFR amplifications in the population of the northeast region of Morocco and then to compare the results with other studies. Methods . IDH1 codon 132 and IDH2 codon 172 were directly sequenced and the amplification of exon 20 of EGFR gene was investigated by qPCR in 65 glioblastoma tumors diagnosed at the University Hospital of Fez between 2010 and 2014. Results . The R132H IDH1 mutation was observed in 8 of 65 tumor samples (12.31%). No mutation of IDH2 was detected. EGFR amplification was identified in 17 cases (26.15%). Conclusion . A systematic search of both histological and molecular markers should be requisite for a good diagnosis and a better management of glioblastomas.